Climate scenarios (CMIP-5) for the Biosphere Reserve of Pantanos de Centla, Tabasco, Mexico - Manzanilla-Quiñones, Ulises; Pozo-Montuy, Gilberto; Delgado-Valerio, Patricia; Martínez-Sifuentes, Aldo Rafael; Aguirre-Calderón, Oscar Alberto (Ecosistemas y Recursos Agropecuarios, 2020)
The present study used precipitation and temperature data between 1960-2015 and Global Circulation Models (GCM) CNRMCM5 and HADGEM2_ES, projected from 2045-2069 and 2075-2099; under two paths of concentrations of greenhouse gas emissions (RCP); 4.5 (constant) and 8.5 (high). The objective was test the hypothesis that the RBPC would become a site highly exposed to the effects of annual temperature average increase and flooding due to sea-level increase. Precipitation and temperature records were downloaded from six meteorological stations and the climatic layers from GMC for 2045-2069 and 2075-2099 (RCP 4.5 and 8.5) at a resolution of 1 km2. The statistical tests used in the data allowed to detect increase trends (p < 0.05) through time. Due to the uncertainty of future climate scenarios, four GCM were tested and analyzed. The results indicate a significant increase trend in annual temperature average from 0.34 to 0.82 ◦C for 1960-2015. The climate scenarios projected that the RBPC would be warmer, drier, and flooded by a sea-level increase from 13 to 33 cm, which would lead to the development of a coastal delta, covering 49.3 to 49.5% of the RBPC during 2045-2099. According to the climatic analyses, the RBPC would show a high climatic exposure in its biological and ecological systems. According to climate analyses, the RBPC would be a highly exposed area to the effects of climate change and sea-level increase. The latter would affect important biogeochemical changes to the freshwater bodies of the area.